Introducing the Berggruen Governance Index I: conceptual and methodological framework - Anheier, Helmut K.; Lang, Markus; Knudsen, Edward (Global policy, 2023)
Governance is at the heart of how well governments meet public needs and manage a wide array of common problems. Why do some countries perform poorly in delivering healthcare, reducing inequality, providing a clean environment or delivering some other public good to their populations even while they have the resources to do so? Does the capacity of states to provide the basics for societies to thrive depend on forms of democratic accountability that represents different interests, or are systems under technocratic control that impose solutions and disregard, even suppress, many voices better at meeting public needs? Existing indices do not systematically examine the relationship between the components that contribute to governance performance. In our understanding of governance, depicted as the Governance Triangle, public goods provision is a function of state capacity and accountability. Rather than focusing on a single composite performance measure, the Berggruen Governance Index examines the interactions among these dimensions. We find that the key to good governance is achieving a balance among the three dimensions on an upward and sustainable trajectory. This article introduces the Index and the conceptual and methodological framework that underpins it and then outlines the content of this special issue.
Gesehen am 08.05.2024